Digital Simulation of Short Circuit Current Calculation Using Graphical User Interface for Learning Media Electric Power System Analysis - Rahmaniar Rahmaniar; Agus Junaidi; Adi Sastra P Tarigan; Abdul Hakim Butar Butar (International Journal of Artificial Intelligence Research, 2022)
The research examines the design of a simulation program for short circuit calculations. A short circuit is an abnormal event called a disturbance in the electric power system. The classification of short circuit consists of three-phase fault, single-phase fault to ground, two-phase fault and two-phase fault to ground. Calculation of short circuit faults in electric power systems is very important for the study of reliability and safety of power systems. The method used in the design of the Graphical User Interface (GUI) based simulation program is the experimental method, which is to identify the magnitude of the short circuit current value based on the theorem of Fortescue's theorem related to symmetrical components. Furthermore, a GUI program script is built for short circuit calculations. The GUI success test was carried out by comparing the results of the short circuit analysis with the short circuit calculation program using Matlab and validation by experts. From the results of testing and validation by experts, it can be seen that the program built can complete the calculation of short circuit faults validly. The GUI SCC program can be applied to electric power system analysis learning, with a media validity level of 0.85, which is good for use in learning. In addition, this study also built a simulation for the calculation of class intervals and the practicality of the media using the Simulink Matlab media, the results of the program design were declared by experts to be valid with an average score of 0.8625